The financial and environmental needs and problems of a group of students with impairments in higher education - Crous, Faan (Acta Academica: Critical views on society, culture and politics, 2007)
Many countries worldwide have legislation to prevent discrimination against students with disabilities and to integrate them into the general education system on secondary and tertiary levels. Moreover, the United Nations and the Commonwealth support and protect the rights of people with disabilities. However, despite legislation locally and abroad, it appears that many remaining barriers prevent people with impairments from full participation in their communities. Against this background, a survey was conducted to determine the environmental and financial needs and problems experienced by a selected group of South African students with impairments in higher education. The students with impairments from three institutions of higher education, who were included in this survey, expressed a need for direct financial support relating to special equipment, discounts on textbooks, part-time employment and decreased tuition fees. Furthermore, they had special requirements for parking space, buildings and lecture rooms.